What the images make in the anthropology? - Almeida Neto, Joaquim Pereira de; Gonçalves, Gabriela Lages; Souza, Jeferson Bastos de; Macedo, Victor Miguel Castillo de (Cadernos de Campo (São Paulo, 1991), 2023)
This dossier, that reunites visual essays coming from different contexts of investigation, teaches us that the images, besides making us see, think, imagine, move, analyze, and deduce, materialize presences and alliances. The six essays published here put us before varied ways of approaching the use of images, bringing sets of ethnographic photographs and of ethnographic drawings, collages, diagrams, mental maps, and archive images. Those visualities, each on its ways, afford reflection on the processes of the ethnographic making, on entered or restricted spaces of intimacy during the fieldwork, and still on the methodologic strategies uses to make see or make understand that which is lived on the encounters between researchers and interlocutors.